MATURAÇÃO IN VITRO DE OÓCITOS DE FELINOS APLICÁVEIS À CAMPO - Larissa Schneider Brandao Souza (2024)
Brandão-Souza, L. S. Maturation in vitro of feline oocytes applicable to field 2024. MASTER'S – Graduate Program in Veterinary Sciences. Faculty of Veterinary Medicine and Animal Science, Federal University of Mato Grosso do Sul, Campo Grande, MS, 2024. The genetic health of a population is the foundation for biodiversity conservation efforts. The development of Assisted Reproduction Technologies (ART) proves to be important tools as they enable the transfer of genetic material between populations, avoiding stress, cost and, implications of transporting animals, as well as reducing the risks of infectious disease transmission. Considering that wild felids are difficult to access (due to their rarity and the fact that individuals are often dispersed in various ex situ management institutions), the use of domestic cats as an experimental model is essential for standardizing various ART techniques. In this context, using portable incubators for in vitro maturation of oocytes (IVM) or even in vitro fertilization of oocytes (IVF) during transport to better-equipped laboratories is important. In this study, maturation rate was evaluated in oocytes incubated in a benchtop incubator (N=114) and a portable incubator (N=116) for 24 hours. Over 60% of oocytes reached the Metaphase II stage in the benchtop incubator (38,5°C, 5% CO2, and 20% O2), whereas approximately 50% reached the same stage in the portable incubator (38,5°C, 5% CO2, and 5% O2), with a difference between treatments (p